A Study of Plastic Waste in Bitumen as A Binder of A Wearing Layer in Flexible Pavement - Kamarum Talib, Muhammad Faiz bin; Abdullah, Mohd Sufyan (Progress in Engineering Application and Technology, 2021)
The increase in plastics use has increased the amount of plastic waste and an increase in traffic on the road surface. This can cause damage to the pavement. For this reason, this study was conducted to study the properties of plastic bitumen and compare the best yield ratio and plastic bitumen design. Six types of plastic bitumen mixtures are available (2.5%, 5.0%, 7.5%, 10%, 15% and 20%). The best ratio obtained is at 2.5% on the penetration test and softening test based on the study. The data obtained for penetration tests were in the range of 60 mm - 70 mm while 45°C - 56°C for softening tests on PEN 60/70 and PEN 80/100. This ratio achieves the specifications set by JKR / SPJ / Rev 2008. For the ductility test, no best ratio is obtained due to not reaching the specifications set by JKR. This is because the technique used is not destroyed. Through this study, bitumen's plastic properties have been obtained, namely, durability, stability, and strength. It can be concluded that the use of bitumen plastic mixture as a binder is highly recommended as it provides an alternative to recycling plastic waste as waste material.